2009
DOI: 10.1128/jvi.01486-09
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Infections ofPepino Mosaic VirusStrains Modulate the Evolutionary Dynamics of this Emergent Virus

Abstract: Pepino mosaic virus (PepMV) is an emerging pathogen that causes severe economic losses in tomato crops (Solanum lycopersicum L.) in the Northern hemisphere, despite persistent attempts of control. In fact, it is considered one of the most significant viral diseases for tomato production worldwide, and it may constitute a good model for the analysis of virus emergence in crops. We have combined a population genetics approach with an analysis of in planta properties of virus strains to explain an observed epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
103
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 73 publications
14
103
2
10
Order By: Relevance
“…Currently, four PepMV genotypes are distinguished: the Peruvian genotype (LP), which was first isolated from Solanum peruvianum and is similar to the original pepino (S. muricatum) isolate (Ló pez et al, 2005;Pagán et al, 2006); the European tomato genotype (EU), which was first reported in greenhouse tomato production in Europe (Mumford and Metcalfe, 2001;Aguilar et al, 2002;Cotillon et al, 2002;Verhoeven et al, 2003;Pagán et al, 2006); the CH2 genotype, which was first isolated from tomato seeds from Chile (Ling, 2007); and the US1 genotype, which was first described in the United States (Maroon-Lango et al, 2005). In recent years, the CH2 genotype has largely replaced the EU genotype in commercial tomato production in several European countries (Hanssen et al, 2008;Gó mez et al, 2009). Two Belgian CH2 PepMV isolates have recently been characterized in detail and were designated mild (isolate 1906, further referred to as the mild CH2 isolate) and aggressive (isolate PCH 06/104, further referred to as the aggressive CH2 isolate) based on symptom expression in naturally infected commercial greenhouse tomatoes and in subsequent greenhouse trials (Hanssen et al, 2009(Hanssen et al, , 2010a.…”
mentioning
confidence: 99%
“…Currently, four PepMV genotypes are distinguished: the Peruvian genotype (LP), which was first isolated from Solanum peruvianum and is similar to the original pepino (S. muricatum) isolate (Ló pez et al, 2005;Pagán et al, 2006); the European tomato genotype (EU), which was first reported in greenhouse tomato production in Europe (Mumford and Metcalfe, 2001;Aguilar et al, 2002;Cotillon et al, 2002;Verhoeven et al, 2003;Pagán et al, 2006); the CH2 genotype, which was first isolated from tomato seeds from Chile (Ling, 2007); and the US1 genotype, which was first described in the United States (Maroon-Lango et al, 2005). In recent years, the CH2 genotype has largely replaced the EU genotype in commercial tomato production in several European countries (Hanssen et al, 2008;Gó mez et al, 2009). Two Belgian CH2 PepMV isolates have recently been characterized in detail and were designated mild (isolate 1906, further referred to as the mild CH2 isolate) and aggressive (isolate PCH 06/104, further referred to as the aggressive CH2 isolate) based on symptom expression in naturally infected commercial greenhouse tomatoes and in subsequent greenhouse trials (Hanssen et al, 2009(Hanssen et al, , 2010a.…”
mentioning
confidence: 99%
“…Desde la detección del PepMV en España se han realizado diferentes estudios detallados para la caracterización genética de las poblaciones españolas del virus Pagán et al, 2006;Gómez et al, 2009) que han demostrado que el virus ha entrado en varias ocasiones en el país. Hasta el año 2004 la mayoría de las infecciones, más del 80%, estaban ocasionadas por infecciones simples de aislados de la cepa "EU".…”
Section: E Es St Tr Ru Uc Ct Tu Ur Ra a Y Y C Co Om Mp Po Os Si Ic Ciunclassified
“…Desde el año 2006, el porcentaje de infecciones mixtas "EU+CH2" y simples de aislados tipo "CH2" ha ido variando en la población de PepMV de la Península. En el año 2008 ambos tipos de infecciones llegaron a igualarse y a representar el 96% de la población mientras que el restante 4% lo constituían infecciones simples de aislados del tipo "EU" (Gómez et al, 2009).…”
Section: E Es St Tr Ru Uc Ct Tu Ur Ra a Y Y C Co Om Mp Po Os Si Ic Ciunclassified
See 2 more Smart Citations